Information systems today : Managing in the digital world / Joseph S. Valacich, Christoph Schneider, Leonard M. Jessup - Valacich, Joseph S.
1. Managing in the Digital World 2. Gaining Competitive Advantage Through Information Systems 3. Managing the Information Systems Infrastructure and Services 4. Enabling Business-to-Consumer Electronic Commerce 5. Enhancing Organizational Communication and Collaboration Using Social Media 6. Enhancing Business Intelligence Using Big Data and Analytics 7. Enhancing Business Processes Using Enterprise Information Systems 8. Strengthening Business-to-Business Relationships via Supply Chain and Customer Relationship Management 9. Developing and Acquiring Information Systems 10. Securing Information Systems Technology Briefing Foundations of Information Systems Infrastructure